MATHEMATICAL POETICS, POETICAL MATHEMATICS - Redaelli, Stefano (PALIMPSEST / ПАЛИМПСЕСТ, 2016)
The Italian literature of the twentieth and twenty-first century offers many examples of writers who have linked, through their literary work, humanistic and scientific culture, as Leonardo Sinisgalli, Carlo Emilio Gadda, Italo Calvino, Gianni Rodari, Paolo Giordano, Piergiorgio Odifreddi. This article shows how mathematical imagination can become poetic imagination. Terms, concepts, theories, languages borrowed from mathematics and physics endow the literary work with epistemic and metaphorical value. For some authors, mathematics is a reservoir of metaphors (such as chemistry was for Levi), for others a reservoir of models used to describe relationships and human systems (that are way more complex than the natural ones), for still others, mathematics becomes the very focus of the story, with a precise educational function.